Elemental state of the organism of workers and population as manifestation of adaptation to the technogenic effect of metals: new methodological approaches - Andrusyshyna , I.М. (Medicni Perspektivi, 2021)
The problem of adaptive, prepathological and pathological reactions of the body to the action of exogenous chemicals is closely intersected with the assessment of the norm and its fluctuations. The imbalance of chemical elements in the human body directly affects the functioning of almost all organs and systems, causing significant stress of adaptation mechanisms. In this article we study the elemental state of the human body depending on the physiological state (endocrine pathology and professional contact with heavy metals), analyze the correlation between macro- and microelements and assess the degree of adaptability of the body. In the work the elemental state of the human body, taking into account not only the absolute values of the concentrations of elements in the hair and whole blood was studied, the adaptability of the body according to the indicators of elemental imbalance in the blood and hair of volunteers, individuals with endocrine pathology (autoimmune thyroiditis and type II diabetes mellitus) and for those working in conditions of contact with heavy metals (for jewelers, welders and batterymen) is analyzed. The results of the study indicate that various non-specific adaptation reactions are accompanied by changes in the elemental state of a person. Under the prevailing pathology of the endocrine system (diabetes mellitus or autoimmune thyroiditis), the adaptation of the body was determined as a stage of tension and is associated with the duration of the disease. In persons exposed to professional contact with heavy metals (Mn, Cr, Pb, Ag), adaptation depended on the nature and duration of professional contact with them: the highest tension of adaptation processes was found in jewelers, and the least in welders and batterymen, which is associated with the duration of professional contact with these metals. The high number of connections between the elements indicates the tension of adaptive reactions in people with endocrine pathology and especially in jewelry workers. Adaptation to the high content of metals in the air of welders and batteries due to the longer experience of these workers and adaptation to production conditions with a decrease in the number of correlations between the elements, as a means of reliable operation.